Measurement of the Parenting Style of the Character of Millennial Students at State Islamic Higher Educational Institutions - Nurmawati, Nurmawati; Panjaitan, Cheri Julida; Amri, Khairul (SCAD Independent, 2022)
The research aimed to determine how to measure parenting style for students who experienced security conflicts or great natural disasters such as tsunamis. The research focused on the parenting style of millennial children, particularly in building their character. The study sample consisted of 210 students at a state Islamic university in Aceh. This study found 38 valid items from the 40 instrument items developed, while two instrument items were invalid because of the rxy value <0 30. Furthermore, the reliability test is conducted by calculating the value of α Cronbach, which found a value of 0 871 for 38 valid items about the instrument. The ANOVA analysis measured the differences of each PTKIN in Aceh (STAIN, IAIN, and UIN). Obtained F value of 3.116 with sig = 0.046. Because the sig value <0.05, Ho is rejected. It can be concluded that there were differences in the average parenting style and student character in UIN, IAIN, and STAIN in Aceh.